The Dionysian Gospel : The Fourth Gospel and Euripides - MacDonald, Dennis Ronald, 1946- (Book collections on Project MUSE., 2017)
"Those who eat my flesh and drink my blood abide in me, and I in them." Dennis R. MacDonald offers a provocative explanation of those scandalous words of Christ from the Fourth Gospel--an explanation that he argues would hardly have surprised some of the Gospel's early readers. John sounds themes that would have instantly been recognized as proper to the Greek god Dionysos (the Roman Bacchus), not least as he was depicted in Euripides's play The Bacchae. A divine figure, the offspring of a divine father and human mother, takes on flesh to live among mortals, but is rejected by his own. He miraculously provides wine and offers it as a sacred gift to his devotees, women prominent among them, dies a violent death--and returns to life. Yet John takes his drama in a dramatically different direction: while Euripides's Dionysos exacts vengeance on the Theban throne, the Johannine Christ offers life to his followers. MacDonald employs mimesis criticism to argue that the earliest Evangelist not only imitated Euripides but expected his readers to recognize Jesus as greater than Dionysos.